(3GdJNWjW GdGSJQGJjLj ddeDSSGJ ZjQ GdQHMjI (B/s - (3GdjShf, eGjcds; (3LGHQ, YHO GdeWdH jhSas; (3GdMehj, eQhGf s ((3GdQjGV(B: s (3ecJHI GdYHjcGJ(B, s, 2007)
(3ebOeI ddJNWjW GdGSJQGJjLj, GdeQMdI GdGhdi(B: (3cf LGgRG, GdeQMdI GdKGfjI(B: (3JJVef GdQSGdI hGdQDjI hGdbje, GdeQMdI GdKGdKI, bje hVYc, GdeQMdI GdQGHYI(B: (3GdGJaGb Ydi GdChdhjGJ, GdeQMdI GdNGeSI(B: (3Ohf GdNWI GdGSJQGJjLjI, GdeQMdI GdSGOSI(B: (3JfajP GdNWI GdGSJQGJjLjI, GdeQMdI GdSGHYI(B: (3bje hQGbH GdNWI GdGSJQGJjLjIs
(3HHdjhZQGajG(B: (3U(B.565-566s
Keywords: (3GJNGP GdbQGQGJs; (3GdJNWjWs; (3GdJNWjW GdEOGQjs